The Transformative Power of Faith: A Narrative Approach to Conversion - Dufault-Hunter, Erin (Lexington Books, 2012)
The Transformative Power of Faith examines how and why some people, particularly those coming out of highly self-destructive, violent, and antisocial backgrounds who appear beyond repair, experience profound personal transformation through conversion to strong faith. Illustrated by stories of converts who came out of serious drug addiction, gangs, and poverty through adherence to a demanding faith, Erin Dufault-Hunter argues for a narrative approach to conversion. This holistic theoretical perspective offers an alternative epistemological stance to reductionistic models sometimes perpetuated among social scientists and religious ethicists alike. In this study, the narrative lens gives vision of the religious “Other” a depth and complexity too often lacking. Such an approach allows a deeper understanding of the dynamics of personal transformation in ways that make sense of psychological and social factors without ignoring so-called “spiritual” ones.